Perfil de micrornas circulantes e gravidade em pacientes com anemia falciforme - Biassi, Thais Priscila [UNIFESP] (2018)
Background: Sickle cell anemia (SCA) is a complex disease, associated with hemolysis, vasoocclusion, vascular inflammation and endothelial activation. Significant morbidity and premature mortality are hallmarks of the disease and elevation of tricuspide regurgitant velocity (TRV), determined by dopplerechocardiography, has been associated with higher risk. The identification of biomarkers associated with severity in SCA is desirable. Circulating serum microRNAs (miRNA) are molecular targets studied in different diseases as diagnostic or prognostic markers, however there are few studies in SCA.Purpose: to identify specific signatures of miRNAs in plasma samples of SCA patients according to severity indexes. Methods: Screening of the miRNAs expression was performed in 8 patients. These patients were classified by TRV measure (referred as TRV Score): 4 samples with TVR ≥ 2.5 m/s and 4 with TRV < 2.5 m/s. After extraction of total RNA, the samples were analyzed by realtime PCR using Megaplex RT Human Pool A and Megaplex RTHuman Pool Blife (Thermofisher) comprising 667 distinct miRNAs. Expression Suite Software (Thermofisher) and SPSS were used for analysis. Seventeen miRNAs were differentially expressed between the two groups (p < 0.05) and miR16 was considered as the endogenous candidate. Five differentially expressed miRNAs (miR15b, miR502, miR510, miR544, miR629) were selected for validation in 56 patient samples using TRV Score. Another two severity scores were also used: (a) Organ Injury Score (SLO) – based on the presence or absence of 5 lesions: stroke, TRV ≥ 2.5 m/s, leg ulcers, osteonecrosis, and microalbuminuria (adapted from AfenyiAnnan et al. Transfusion 2008; 48:197) and (b) NIH Bayesian score – available online (http://bios.ugr.es/dsscalculator/). The ROC curve was used to analyze the data of relative expression (2ΔCT) of each miRNA.Results: Two out of five miRNA, miR510 and miR629, were significantly decreased in more severe patients. The miR510 expression allowed the discrimination of the patients according to TRV Score at the cutoff 0,000367664, sensitivity 68,4%, specificity 81.2% and 0,773 (95% IC: 0,6110,935, p = 0,006). The same miRNA was also a good discriminant in the SLO at a cutoff of 0.000331043, sensitivity 70,6%, specificity 72.2% and area under the curve (AUC) of 0.716 (95% CI: 0,5370,894) p = 0.029.The miR629 was related to severity according to the Bayesian Score at the cutoff of 0.0009854449, sensitivity 66.7%, specificity 75% and AUC of 0.729 (95% CI: 0,5270,897, p=0,047). The other miRNAs, miR15b, miR502 and miR544, showed no significant results.Discussion and Conclusions: This is the first study thatlooks into plasma miRNA as a biomarker of SCA severity. The miR510 regulate Peroxirredoxin1 (PRDX1), a protein involved in the stressoxidation. Increased oxidative stress presented in SCA might imply that miR510 has a role in this mechanism. The miR629 appears to be involved in the AKT1 signaling pathway related to Endothelin1. As it is known, endothelin1 is increased in SCA and is important in pulmonary hypertension. The miR510 and miR629 appear to be hypoexpressed in patients with more severe SCA, probably with greater importance in the regulation of clinical manifestations associated with vascular disease, although more studies seem to be necessary.